2019
DOI: 10.3390/molecules24112183
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Studies on the Protocol and Criteria for Selecting a Covalent Docking Tool

Abstract: With the resurgence of drugs with covalent binding mechanisms, much attention has been paid to docking methods for the discovery of targeted covalent inhibitors. The existence of many available covalent docking tools has inspired development of a systematic and objective procedure and criteria with which to evaluate these programs. In order to find a tool appropriate to studies of a covalently binding system, protocols and criteria are proposed for protein–ligand covalent docking studies. This paper consists o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 49 publications
0
31
0
1
Order By: Relevance
“…Though many covalent docking tools have been developed, covalent docking is still rarely used in virtual screening since it is quite timeconsuming in comparison to noncovalent docking. 32 A recent study demonstrated that covalent docking does not perform significantly better than noncovalent docking. Conversely, noncovalent docking successfully predicts correct binding conformations for many covalent complexes that are failed in covalent docking.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though many covalent docking tools have been developed, covalent docking is still rarely used in virtual screening since it is quite timeconsuming in comparison to noncovalent docking. 32 A recent study demonstrated that covalent docking does not perform significantly better than noncovalent docking. Conversely, noncovalent docking successfully predicts correct binding conformations for many covalent complexes that are failed in covalent docking.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Virtual screening is performed against the selected binding pocket using the covalent NP database. Though many covalent docking tools have been developed, covalent docking is still rarely used in virtual screening since it is quite time-consuming in comparison to noncovalent docking . A recent study demonstrated that covalent docking does not perform significantly better than noncovalent docking.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that for an ideal covalent-docking tool, the success rate should not be dependent on protein classes, ligand warhead classes, residue types, and reaction mechanisms [ 93 ]. However, the performance of the present covalent-docking tools is largely dependent on these aforementioned criteria.…”
Section: Selecting An Ideal Covalent-docking Program For Virtual-scre...mentioning
confidence: 99%
“…Protein docking-based methods directly predict the interaction between host receptor protein and the spike protein of SARS-CoV-2. The protein docking algorithms are divided into rigid and flexible ones (Sable and Jois, 2015;Lensink et al, 2016;Xu et al, 2018;Wen et al, 2019). Rigid docking methods like ZDOCK (Pierce et al, 2014) and MEGADOCK (Ohue et al, 2014) are usually simple and less time-consuming.…”
Section: Introductionmentioning
confidence: 99%